Providing Equity of Access to Higher Education in Indonesia: A Policy Evaluation - Ihsan Fadhil; Amra Sabic-El-Rayess (Universitas Muhammadiyah Surakarta, 2021)
In the last decade, Indonesia has worked towards expanding access to higher education, but the enrolment of the poor remains negligible with the majority of students in the country’s leading public universities still coming from Indonesia’s wealthiest echelons. Concerned with the issue of equity and access, the government has formulated a new policy calling on all higher education institutions to ensure at least 20% of their newly admitted students are of a low socioeconomic status (SES). The principal challenge the government has faced is a discrepancy between its ambitious political agenda and the policy’s implementation affected by inadequate budgeting, lacking implementation mechanisms, and limited award allocations. This challenge raises a question of whether the Equity and Access Policy can be effectively implemented and, if so, under what conditions can such success be achieved. We thus examine the country’s Equity and Access Policy, education system with its leadership structure, broader institutional framework, and how these factors interact to obstruct the higher education access for the poor in Indonesia. The inadequate policy implementation can impede Indonesia’s human capital development and the country’s economic growth.